2013
DOI: 10.1107/s0108767313094956
|View full text |Cite
|
Sign up to set email alerts
|

Solid acid proton conductors: the influence of hydrogen subsystems on physical properties

Abstract: Interest in superprotonic crystals of M m H n (XO 4 ) (m+n)/2 (М = K, Rb, Cs, NH 4 ; X = S, Se, P) is associated with the solution to fundamental problems of modern condensed matter physics: establishment of structural conditionality of anomalies of physical properties with the aim of designing new functional materials. Superprotonic crystals belong to a special class. As opposed to other hydrogen-containing compounds, phase transitions in these crystals are accompanied by a hydrogen-bond network rearrangement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In K 3 H(SO 4 ) 2 [8] and K 9 H 7 (SO 4 ) 8 ⋅ Н 2 О [11] crystals, which also belong to the M m H n (XO 4 ) (m + n)/2 ⋅ yН 2 О family, the mean S-O bond lengths in SO 4 tetrahedra are, respectively, 1.481(1) and 1.468(2)-1.476(2) Å. Despite the difference in the systems of hydrogen bonds, the S-O bond lengths in these compounds are also close to the corresponding values for CsHSO 4 crystals.…”
Section: Synthesis and Characterization Of Crystalline Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…In K 3 H(SO 4 ) 2 [8] and K 9 H 7 (SO 4 ) 8 ⋅ Н 2 О [11] crystals, which also belong to the M m H n (XO 4 ) (m + n)/2 ⋅ yН 2 О family, the mean S-O bond lengths in SO 4 tetrahedra are, respectively, 1.481(1) and 1.468(2)-1.476(2) Å. Despite the difference in the systems of hydrogen bonds, the S-O bond lengths in these compounds are also close to the corresponding values for CsHSO 4 crystals.…”
Section: Synthesis and Characterization Of Crystalline Samplesmentioning
confidence: 99%
“…A structural analysis of K 9 H 7 (SO 4 ) 8 ⋅ Н 2 О crystals (which are currently a single representative of the M 9 H 7 (XO 4 ) 8 ⋅ yН 2 О subgroup) with the aid of X-ray and synchrotron radiation beams [10,11] showed that the main changes in the atomic structure of crystals at a phase transition are related to the diffusion of crystallization water and subsequent transformation of the system of hydrogen bonds. As a result, a new system of hydrogen bonds is formed which is partially dynamically disordered and contains additional sites for protons.…”
Section: Introductionmentioning
confidence: 99%